2017
DOI: 10.1111/ijfs.13424
|View full text |Cite
|
Sign up to set email alerts
|

Wine authentication with Fourier Transform Infrared Spectroscopy: a feasibility study on variety, type of barrel wood and ageing time classification

Abstract: Wine aging in wooden barrels improves the final products' sensory profile and increases the price. Among the different types of woods, the International Enological Codex of the International Organisation of Vine and Wine (OIV) approves only the use of Oak and Chestnut, thus producing a need for fast and costeffective authentication methods. In this study Fourier Transform (FT)-mid-infrared (IR) spectroscopy combined with chemometrics was employed to analyze and discriminate wines aged in barrels made from diff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
23
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(25 citation statements)
references
References 31 publications
2
23
0
Order By: Relevance
“…Based on the bands from 1600 cm -1 , the polyphenolic content was also evaluated [7]; -to develop a rapid and simple method for wine authenticity [8]; * email: carmen.topala@gmail.com; Tel. : 0745981621 -authentication with a feasibility study on variety, type of barrel wood and ageing time classification of wine [9];…”
Section: Sefanesti-argesmentioning
confidence: 99%
“…Based on the bands from 1600 cm -1 , the polyphenolic content was also evaluated [7]; -to develop a rapid and simple method for wine authenticity [8]; * email: carmen.topala@gmail.com; Tel. : 0745981621 -authentication with a feasibility study on variety, type of barrel wood and ageing time classification of wine [9];…”
Section: Sefanesti-argesmentioning
confidence: 99%
“…Certainly, IR spectroscopy coupled with multivariate data analysis has been used for the determination of oak volatile compounds [101][102][103] and for classifying barrels [104]. Subsequently, in recent years, this method has been proposed for discriminating wines aged in different types of wood containers and for different time periods [96,105,106], taking advantage on PLS-based calibration between GC-MS and near infrared spectroscopy (NIR).…”
Section: Discrimination Based On Spectroscopy Methodsmentioning
confidence: 99%
“…For instance, FT-IR and UV-visible (UV-Vis) spectroscopic techniques combined with multivariate analysis were used to obtain regression models to study the aging level of high-quality Sherry wines [106]. Moreover, [105] wines aged in barrels made from different wood species and in stainless steel tanks, were analyzed. A complete differentiation of the samples was achieved according to grape variety, the container type and the aging time based on two spectral regions of their FT-IR spectra.…”
Section: Discrimination Based On Spectroscopy Methodsmentioning
confidence: 99%
“…It is for this reason that the process used during wine ageing needs to be traceable for insurance of trustworthy trading standards. Basalekou et al [71] demonstrated the ability of Vis-NIRS to discriminate different wines based on variety, type of barrel and ageing time. Magdas et al [72] demonstrated rapid discrimination of wines based on variety, vintage and geographic origin.…”
Section: The Application Of Vis-nirs On Secondary Products From Fruitsmentioning
confidence: 99%